ANALISIS PENGARUH PENGELUARAN PEMERINTAH DAN INVESTASI TERHADAP PEMBANGUNAN MANUSIA MELALUI PERTUMBUHAN EKONOMI DAERAH ISTIMEWA YOGYAKARTA - Rahajeng Neysa Alifia; Moh. Khusaini (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
The achievement of human development is frequently interconnected with the economic growth. Fiscal decentralization allows local governments to enhance budget management in order to stimulate economic growth through expenditure and investment. Despite having the second highest Human Development Index (HDI) in Java, the Special Region of Yogyakarta faces difficulties of being the province with the lowest economic growth in Java. Hence, the government's involvement in allocating funds towards education, healthcare, and investment is crucial in fostering economic growth and promoting human development. This study used path analysis technique to investigate the correlation between government expenditure on education and health services, as well as the investment in human development through economic growth in the District/City of Yogyakarta Special Region. The data used is secondary data collected between 2015-2021, encompassing four districts and one city. The research using the trimming model revealed that government expenditure on the education sector has a noteworthy adverse impact on HDI, albeit indirectly, affecting economic growth. Government expenditure on healthcare has an indirect but significant positive impact on the HDI via promoting economic growth. Conversely, investment does not exert a substantial impact, either directly or indirectly on HDI.